Increasing the Competitive Advantage of MSMEs in the COVID-19 Pandemic Era by Implementing the Blue Ocean Strategy: A Case Study on RM Dikamali’ - Mey Enggane Limbongan; Astriwati Biringkanae (Manajemen Bisnis, 2021)
The high risk of bankruptcy in micro-enterprises, that occurs during the COVID-19 pandemic, makes the micro-business segment experience the biggest impact of the decline in revenue due to limited supply and demand. History notes that during the 1998 economic crisis, MSMEs contributed 39.40% to GDP and were able to absorb 88.90% of workers. However, the situation in the COVID-19 pandemic is different from the situation in the 1998 economic crisis, in which technological developments are quite rapid in the current era. The rapid development of technology has led to increasingly strong pressure for companies to be able to achieve a competitive advantage. This study aims to identify and elaborate the application of the blue ocean strategy to MSMEs to increase competitive advantage. The innovation steps taken were evaluated with the Canvas Strategy and ERRC Grid. In addition, the researchers also applied the SWOT matrix as a starting point for mapping external and internal potentials. The results of this study indicated RM Dikamali’ has met three good criteria for implementing the blue ocean strategy, namely having focus, moving away from existing competitors, and having an attractive slogan. RM Dikamali’ took six stages in implementing the blue ocean strategy, making them be able to get out of market constraints and open new markets. The results of this study can be used as a reference for further studies concerning the Blue Ocean Strategy and for MSMEs in implementing the blue ocean strategy to increase their competitive advantage.